Development Study of Binding Agent in Diffusive Gradient In Thin Films (DGT) Technique for Absorption of Phosphate Compounds using Nano-La2O3 - Hanna Shafira; Rika Tri Yunarti; Asep Saefumillah (Syarif Hidayatullah State Islamic University, 2022)
The abundance of phosphate is a concern because it causes problems in aquatic ecosystems. The diffusive gradient in thin films (DGT) technique is a promising method for phosphate absorption because it can be used in situ. The DGT device consists of a membrane filter, a diffusive gel, and a binding gel. The presence of a binding agent in the binding gel makes the specific analyte bound to the binding gel. One of the binding agents that can be used for phosphate absorption is La2O3. Binding gel La2O3 was successfully synthesized that proven by the similarity of FTIR peaks of the diffusive gel and binding gel. The typical absorption of La-O also proves it from the binding gel at 642 cm-1 and 423 cm-1. La2O3 binding gel was made of N,-N'-methylenebisacrylamide as a cross-linker with an elution factor of 97.4%. DGT-La2O3 proved capable of adsorption for 72 hours, with phosphate absorbed at 1.91 x 105 ng. DGT-La2O3 also has the optimum ability to absorb phosphate at pH 3 of 1.93 x 105 ng.